2016
DOI: 10.1007/s40262-016-0453-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Venetoclax Exposure on Clinical Efficacy and Safety in Patients with Relapsed or Refractory Chronic Lymphocytic Leukemia

Abstract: The exposure-response analyses indicated that a venetoclax dosage regimen of 400 mg daily results in a high (>80 %) probability of achieving OR in R/R CLL/SLL patients, with minimal probability of increasing neutropenia or infection with higher exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 38 publications
1
57
0
Order By: Relevance
“…With regard to safety, subjects receiving venetoclax doses up to 1200 mg once daily, where the exposures were approximately 2.5‐fold higher than those achieved at the approved dose of 400 mg once daily, did not experience dose‐limiting toxicities . Consistently, exposure–safety analyses indicated that higher venetoclax exposures had no effect on QT interval and were not associated with an increase in grade 3 or higher adverse events of neutropenia and infection . Based on these exposure–response relationships and assuming that a similar exposure–response relationship exists in Chinese subjects with CLL, the phase 2 open‐label study evaluating the venetoclax pharmacokinetics, efficacy, and safety in Chinese subjects with R/R CLL is being conducted at the 400‐mg once‐daily dose.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…With regard to safety, subjects receiving venetoclax doses up to 1200 mg once daily, where the exposures were approximately 2.5‐fold higher than those achieved at the approved dose of 400 mg once daily, did not experience dose‐limiting toxicities . Consistently, exposure–safety analyses indicated that higher venetoclax exposures had no effect on QT interval and were not associated with an increase in grade 3 or higher adverse events of neutropenia and infection . Based on these exposure–response relationships and assuming that a similar exposure–response relationship exists in Chinese subjects with CLL, the phase 2 open‐label study evaluating the venetoclax pharmacokinetics, efficacy, and safety in Chinese subjects with R/R CLL is being conducted at the 400‐mg once‐daily dose.…”
Section: Discussionmentioning
confidence: 86%
“…The approved therapeutic dosage regimen of venetoclax is 400 mg once daily in patients with CLL after the initial weekly ramp‐up. In an exposure–efficacy analysis conducted using data from subjects with CLL (predominantly whites), the rate of objective response was shown to be similar, with a 0.5‐ to 2.0‐fold change in venetoclax exposure from that typically achieved at the 400‐mg once‐daily dosage regimen . An exposure progression‐free survival (PFS) analysis demonstrated that higher exposures are likely to increase PFS .…”
Section: Discussionmentioning
confidence: 98%
“…Recently, venetoclax was approved by the US FDA for treatment of newly diagnosed AML in adults who are aged 75 years or older or who have comorbidities that preclude use of intensive induction chemotherapy in combination with HMAs or LDAC under accelerated approval pathway. Previous studies have evaluated the venetoclax exposure response relationships in subjects with CLL, non‐Hodgkin's lymphoma, or multiple myeloma . The findings of the analyses reported herein provide the rationale and justification for the dose of venetoclax used in the pivotal, global, randomized, double‐blind, placebo‐controlled phase III study in combination with azacitidine versus azacitidine alone (NCT02993523) and in combination with LDAC vs LDAC alone (NCT03069352), conducted in treatment‐naïve elderly patients with AML who are ineligible for standard induction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant use of moderate CYP3A inhibitors increased dose‐normalized venetoclax C max and AUC 0‐24 values by 40% to 60%. An exposure‐safety analyses of the adverse events (grade ≥ 3) in CLL patients indicated that higher average venetoclax concentrations were associated with a decrease in neutropenia rates likely due to disease improvement . However, because of the risk for tumor lysis syndrome during the ramp‐up phase, coadministration of venetoclax with moderate CYP3A inhibitors should be avoided, or the venetoclax dose should be reduced during the ramp‐up phase in CLL patients.…”
Section: Discussionmentioning
confidence: 99%